Behavior of Structural Concrete Frames with Hybrid Reinforcement under Cyclic Loading (Fracture and Structural Integrity, 2021)
A substantial amount of work was carried out on the use of fiber-reinforced polymer (FRP) in reinforcing concrete structural elements, which demonstrated considerable inelasticity or deformity through monotonous and fatigue loads. Even so, the action of FRP bars in FRP-RC columns and frame structures has not yet been studied during reversed cyclic loading.In this research, reversed cyclic loading was conducted on three beam-column joint models using the finite element method with ANSYS software. The first model was for a joint designed with steel rebar for both the longitudinal reinforcement and stirrups. Glass fiber reinforced polymer (GFRP) rebar was used to reinforced the second joint model for both longitudinal reinforcement and steel stirrups, and the third joint model was designed with hybrid steel/GFRP reinforcement for the longitudinal reinforcement and steel stirrups. The performance of the three models under reversed cyclic loading, such as load vs. story drift and energy dissipation capacity, were compared. The GFRP-reinforced model displayed a predominantly elastic activity up to failure. Although its energy dissipation was weak, its performance in terms of total storey drift demand was satisfactory.
Keywords: GFRP; Hybrid reinforcement; cyclic loading; beam-column joint; frames